Offspring birth weight and cardiovascular mortality among parents: the role of cardiovascular risk factors. (15th February 2018) - Shaikh, F.; Kjøllesdal, M. K.; Naess, Ø.
Abstract: An inverse association between offspring birth weight (BW) and higher risk of parental cardiovascular disease (CVD) mortality and morbidity has been reported. Shared environmental, genetic and intrauterine factors may be responsible for explaining these associations. We studied the role of parental CVD risk factors in the association between offspring BW and CVD mortality among mothers and fathers. All births registered in Medical Birth Registry Norway (1967–2012) were linked to three health surveys, National Educational Registry and Cause of Death Registry. Number of births with information of parental CVD risk factors available for the analyses was 1, 006, 557 (520, 670 for mothers and 485, 887 for fathers). Cox proportional hazards regression models were used, following CVD deaths in parents from 1974 to 2012. An inverse association between offspring BW and CVD mortality was observed among both parents: hazard ratio 1.60 (1.44–1.75) for mothers and 1.16 (1.10–1.23) for fathers. Among mothers, adjustment for smoking, triglycerides and diabetes reduced the risk to 1.36 (1.25–1.52), 1.57 (1.43–1.73) and 1.58 (1.43–1.79), respectively. Adjustment for diastolic blood pressure (DBP) and systolic blood pressure (SBP) both reduced the risk to 1.53 (1.37–1.66). Among fathers, adjustments for smoking, DBP, SBP reduced the risk to 1.08 (1.02–1.15), 1.13 (1.06–1.19) and 1.14 (1.08–1.22), respectively. Triglycerides and diabetes both reduced the risk to 1.15 (1.09–1.12). Our results indicate that shared environmental factors might be important in the association. A stronger association in mothers suggest that intrauterine factors also are at play.